Variation in recorded child maltreatment concerns in UK primary care records: a cohort study using The Health Improvement Network (THIN) database. - Jenny Woodman; Nick Freemantle; Janice Allister; Simon de Lusignan; Ruth Gilbert; Irene Petersen (PLoS ONE)
Objectives To determine variation over time and between practices in recording of concerns related to abuse and neglect (maltreatment) in children's primary care records. Design Retrospective cohort study using a United Kingdom representative primary care database. Setting 448 General Practices. Participants In total 1,548, 972 children (<18 y) registered between 1995 and 2010. Main outcome measures Change in annual incidence of one or more maltreatment-related codes per child year of registration. Variation between general practices measured as the proportion of registered children with one or more maltreatment-related codes during 3 years (2008-2010). Results From 1995-2010, annual incidence rates of any coded maltreatment-related concerns rose by 10.8% each year (95% confidence interval 10.5, 11.2; adjusted for sex, age and deprivation). In 2010 the rate was 9.5 per 1000 child years (95%CI: 9.3, 9.8), equivalent to a prevalence of 0.8% of all registered children in 2010. Across all practices, the median prevalence of children with any maltreatment-related codes in three years (2008 to 2010) was 0.9% (range 0%-13.4%; 11 practices (2.5%) had zero children with relevant codes in the same period). Once we accounted for sex, age, and deprivation, the prevalence for each practice was within two standard errors of the grand mean. Conclusions General Practitioners (GPs) are far from disengaged from safeguarding children; they are consistently and increasingly recording maltreatment concerns. As these results are likely to underestimate the burden of maltreatment known to primary care, there is much scope for increasing recording in primary care records with implications for resources to respond to concerns about maltreatment. Interventions and policies should build on this evidence that the average GP in the UK is engaged in child safeguarding activity.